1997
DOI: 10.1108/09600039710175895
|View full text |Cite
|
Sign up to set email alerts
|

Organization for logistics: the contingency approach

Abstract: Argues that the organization for logistics often favours an aggregation of all tasks into one department. This decision presupposes an extensive analysis of important contingency factors, like product line, environmental relations, technology and organizational size. However, such contingency factors have a limited influence, and are modified by the strategy of the organization. Defines selected contingency factors, examines the organization’s overall strategy and shows how these two factors can be combined in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 23 publications
0
25
0
Order By: Relevance
“…Other research has identified differences among firms with respect to span of control on the basis of the following: organizational growth (Pfohl and Zöllner 1987;Hanks and Chandler 1994), organizational structure (Dröge and Germain 1989), and characteristics of the top functional executive (Salancik and Pfeffer 1977). This research, therefore, suggests that changes to span of control occur as firms grow, as organizational structures change, and as new functional executives (e.g., chief purchasing officer) are appointed.…”
Section: Previous Research Functional Span Of Controlmentioning
confidence: 82%
“…Other research has identified differences among firms with respect to span of control on the basis of the following: organizational growth (Pfohl and Zöllner 1987;Hanks and Chandler 1994), organizational structure (Dröge and Germain 1989), and characteristics of the top functional executive (Salancik and Pfeffer 1977). This research, therefore, suggests that changes to span of control occur as firms grow, as organizational structures change, and as new functional executives (e.g., chief purchasing officer) are appointed.…”
Section: Previous Research Functional Span Of Controlmentioning
confidence: 82%
“…Aronsson and Huge-Brodin [8], Kalenoja, et al [25], McKinnon [39], Pfohl and Zöllner [23] Establishing responsibilities for the environment and transported products, just-in-time deliveries, returns…”
Section: Logistics Systemmentioning
confidence: 99%
“…Managers have always sought the best way to deal with the broad scope of supply chain management decisions and have focused on how different supply chain objectives should be prioritized. Pfohl and Zollner (1997) indicate that the answer to these questions requires an extensive analysis of important logistical contingency factors and their relationships to supply chain management choices. Under a contingency perspective, the right thing to do depends on contextual factors.…”
Section: Contingency Approach To Supply Chain Managementmentioning
confidence: 99%